(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
In this paper explores English phraseological combinations and Uzbek compound nouns delves into two distinct linguiatic phenomena that the lexicon an dexpress complex meanings in their respective languages. While bothinvolve the combinationof multiple elements to form new semantic units, their structural,semantic and functional characteristic differ significantly.